International politics and society (Bonn Verlag J.H.W., 2006)
"IPG journal sees itself as a platform for lively debate questions of international and European politics. We want to not only describe, but also give impetus by critical interpretations and evaluations. The range of topics includes foreign, security, and development issues as well as challenges of European integration and global environmental issues" from IPG website
last issue received #4 (2010). the last edition of journal International Politics and Society was published in November 2011.
Keywords: Political Science; POLITICS; INTERNATIONAL POLITICS; INTERNATIONAL SECURITY; ECONOMIC DEVELOPMENT; PERIODICALS